ANALISIS RISIKO SISTEM INFORMASI AKUNTANSI MENGGUNAKAN ISO 31000:2018 DI PT. XYZ - Filikano, Thomas; Gunawan, Andronikus; Andayani, Sri (LPPM Universitas Bina Bangsa, 2024)
In the dynamic business environment, risk management plays a crucial role in the sustainability and success of a company. This research aims to assist PT. XYZ, a local beverage distribution company, in identifying, analyzing, and managing the risks it faces using the ISO 31000:2018 approach. A case study research method is applied, focusing on the company's accounting information system. Risk assessment steps include identifying assets, potential risks, and risk impacts, followed by analyzing the likelihood and impact of risks. The analysis results classify risks into three levels: Low, Medium, and High. Out of the 18 identified risks, risk treatment is conducted by providing appropriate solutions to mitigate the identified risks, as listed in the recommendation table. It is hoped that the findings of this analysis will help PT. XYZ minimize losses caused by risks and enhance its business sustainability